2010
DOI: 10.1007/s10509-010-0519-3
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type-VI0 cosmological models with anisotropic dark energy

Abstract: The anisotropic nature of the dark energy for Bianchi type-VI 0 space time is discussed. The exact solution of the Einstein field equations under the assumption on the anisotropy of the fluid are obtained for exponential and power-law volumetric expansions. The isotropy of the fluid, space and expansion are examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The anisotropy parameter of the expansion is crucial to determine whether the models approach isotropy or not. It is observed that the value of anisotropy parameter A m given by (22) is similar to A m 's obtained for Bianchi type-I, Bianchi type-III, Bianchi type-V, Bianchi type-VI 0 , Hypersurface-homogenous and Kantowaski-Sachs in General Relativity (Kumar and Singh 2007;Singh and Baghel 2009;Singh et al 2008;Kilinc 2010a, 2010b;Adhav et al 2011aAdhav et al , 2011bSingh and Beesham 2011a). Using the energy-momentum tensor (21), the field equations (7)-(10) now read…”
Section: Some Basic Equationssupporting
confidence: 63%
“…The anisotropy parameter of the expansion is crucial to determine whether the models approach isotropy or not. It is observed that the value of anisotropy parameter A m given by (22) is similar to A m 's obtained for Bianchi type-I, Bianchi type-III, Bianchi type-V, Bianchi type-VI 0 , Hypersurface-homogenous and Kantowaski-Sachs in General Relativity (Kumar and Singh 2007;Singh and Baghel 2009;Singh et al 2008;Kilinc 2010a, 2010b;Adhav et al 2011aAdhav et al , 2011bSingh and Beesham 2011a). Using the energy-momentum tensor (21), the field equations (7)-(10) now read…”
Section: Some Basic Equationssupporting
confidence: 63%
“…Thus models with anisotropic background which approach to isotropy at late times has given much importance for describing the evolution of the universe. Adhav et al (2012), Katore et al (2012), Kumar and Yadav (2011), and many researchers have studied cosmological models in presence of anisotropic dark energy. Das and Sultana (2015) have recently studied magnetized anisotropic ghost dark energy model.…”
Section: Introductionmentioning
confidence: 99%
“…Among them we are interested in Bianchi type spatially homogeneous and anisotropic DE models which are very important to study the evolution of our universe at its early stages and to describe the small amounts of anisotropy at the beginning of the universe. A host of authors have investigated spatially homogeneous and anisotropic DE models both in general relativity and in modified theories of gravitation [16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26] (we mention only some of them). Also it is useful to construct viable Bianchi type scalar field DE models in the framework of particle physics that is DE models in the presence scalar-meson fields and massive scalar fields in general relativity.…”
Section: Introductionmentioning
confidence: 99%